Empirical derivation of upper and lower bounds of NBTI aging for embedded cores. (January 2018) - Chen, Yukai; Macii, Enrico; Poncino, Massimo
Abstract: In deeply scaled CMOS technologies, device aging causes transistor performance parameters to degrade over time. While reliable models to accurately assess these degradations are available for devices and circuits, the extension to these models for estimating the aging of microprocessor cores is not trivial and there is no well accepted model in the literature. This work proposes a methodology for deriving an NBTI-induced aging model for embedded cores. Since aging can only be determined on a netlist, we use an empirical approach based on characterizing the model using a set of open synthesizable embedded cores, which allows us to establish a link between the aging at the transistor level and the aging from the core perspective in terms of maximum frequency degradation. Using this approach, we were able to (1) prove the independence of the aging on the workloads which run by the cores, and (2) calculate upper and lower bounds for the "aging factor" that can be used for a generic embedded processor. Results show that our method yields very good accuracy in predicting the frequency degradation of cores due to NBTI aging effect, and can be used with confidence when the netlist of the cores is not available. Highlights: NBTI aging degradation of the embedded cores is independent of the workload. A fixed aging factor can be interpreted as an equivalent signal probability to be used in a traditional transistor-level aging model. The characterization on different cores generates lower and upper bounds for the aging factor. An NBTI aging micromodel proposed for a core that expresses the worst and best case frequency degradation based on the aging factor range.